2009
DOI: 10.1016/j.expneurol.2008.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic denervation and spine loss in the striatum of MPTP-treated monkeys

Abstract: Striatal spine loss is a key pathological feature of human Parkinson’s disease (PD) that can be induced after complete degeneration of the nigrostriatal dopaminergic system in rodent models of parkinsonism. In line with these observations, our findings reveal a significant (30–50%) reduction in spine density in both the caudate nucleus and putamen of severely DA-depleted striata of MPTP-treated monkeys; the sensorimotor post-commissural putamen being the most severely affected region for both dopamine depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
151
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(179 citation statements)
references
References 37 publications
18
151
2
1
Order By: Relevance
“…Thus, we hypothesize here a close relationship between the ethanol withdrawal-induced reduction of DAergic activity and the loss of dendritic spines in the Nacc shell. Such a conclusion would also be consistent with results obtained using 6-hydroxydopamine lesions (30) and the consequent marked decrease in MSN spine density (31)(32)(33). It is also supported by previous data showing that morphine-withdrawn (34) and cannabis-dependent subjects (35) display a loss of dendritic spines paralleled by a reduced DAergic firing (36,37) and impaired DA release (38)(39)(40).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, we hypothesize here a close relationship between the ethanol withdrawal-induced reduction of DAergic activity and the loss of dendritic spines in the Nacc shell. Such a conclusion would also be consistent with results obtained using 6-hydroxydopamine lesions (30) and the consequent marked decrease in MSN spine density (31)(32)(33). It is also supported by previous data showing that morphine-withdrawn (34) and cannabis-dependent subjects (35) display a loss of dendritic spines paralleled by a reduced DAergic firing (36,37) and impaired DA release (38)(39)(40).…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have pointed to D 1 -expressing (direct pathway) MSNs as being critical to the development and maintenance of dyskinesias (Bordet et al 2000;Carta et al 2008;Berthet et al 2009;Darmopil et al 2009). In contrast, rodent studies indicate that MSN dendritic spine loss in the dopamine-depleted striatum occurs in D 2 -expressing MSNs (Rodriguez and Pickel 1999;Day et al 2006;Deutch et al 2007), although a recent study in the primate suggests that spines are also lost on D 1 -expressing cells (Villalba et al 2009). Because Golgi impregnation of neurons precludes the determination of the type of MSN, we cannot ascertain if the changes we observed occur in indirect-or direct-pathway MSNs.…”
Section: Relation To Motor Deficits In Parkinsonismmentioning
confidence: 94%
“…Among these disorders is PD, in which striatal dopamine depletion elicits dystrophic changes of MSN dendrites. Both postmortem studies of PD as well as studies in animal models of parkinsonism have reported a marked decrease in MSN spine density (McNeill et al 1988;Ingham et al 1989Ingham et al , 1993Ingham et al , 1998Arbuthnott et al 2000;Stephens et al 2005;Zaja-Milatovic et al 2005;Day et al 2006;Villalba et al 2009). While the primary cause of this dendritic remodeling is loss of dopamine signaling through the D 2 receptor (Day et al 2006;Deutch et al 2007), it appears likely that changes in cortically derived glutamate contribute to the changes in MSN spines.…”
Section: Introductionmentioning
confidence: 99%
“…Irregularities in dopamine production and/or dopamine receptors are linked to disorders such as autism, schizophrenia, depression, ADHD, and substance abuse. Abnormally high or low levels of dopamine negatively impact dendritic morphology (22,68,69). In a thorough review of the impact of dopamine on brain disorders and neurodevelopment, Money and Stanwood (68) state that examination of all the evidence points to dopamine playing "a crucial role…in formation and stabilization of synaptic connections in the striatum and frontal cortex".…”
Section: Dopamine Reuptake Inhibitionmentioning
confidence: 99%